The Language issue in education - Acuña, Jasmin E.; Cruz, Isagani R. ;Manalang, Pricila S. ;Miranda, Bienvenido T. ;Sibayan, Bonifacio P. (Manila, Philippines : Congressional Oversight Committee on Education, 1994)
Probably the most critical issues in education today are language of instruction and erosion of values. We see the two as interrelated. Language encodes the cultural values of a people. It encodes their shared experiences, shared aspirations that unite them as one social group. Filipinos have eight major languages and some 156 minor languages, hence the problem of communication ensues. Filipinos love their native languages and the problem of what language should be used as medium of instruction remains unresolved.
A closer look at the language controversy -- Language of teaching reconsidered -- Philippine language problems -- Language of instruction in science education -- Language of instruction in the humanities.
Includes bibliographical references.
Keywords: LANGUAGE EDUCATION